Evaluation of antimicrobial activity of the hydrolate of Coridothymus capitatus (L.) Reichenb. fil. (Lamiaceae) alone and in combination with antimicrobial agents - Andreana Marino; Antonia Nostro; Narcisa Mandras; Janira Roana; Giovanna Ginestra; Natalizia Miceli; Maria Fernanda Taviano; Fabrizio Gelmini; Giangiacomo Beretta; Vivian Tullio (BMC, 2020)
Abstract Background Hydrolates, complex mixtures containing traces of essential oils (EOs), are inexpensive, easy to make and less toxic than their corresponding EOs. The antibacterial and antifungal activity of the hydrolate of Coridothymus capitatus (L.) Reichenb. fil. (Lamiaceae) alone and in combination with antimicrobial drugs, such as tetracycline and itraconazole, were evaluated. Methods The chemical composition was analysed by gas-chromatography-mass spectrometry (GC-MS). Standard methods were performed to evaluate the susceptibility of some Gram-positive and Gram-negative bacteria, and Candida spp. to the hydrolate, in comparison with its EO. The hydrolate mechanism of action was assayed by propidium iodide and MitoTracker staining. Checkerboard tests were carried out for combinations studies. Results GC-MS identified 0.14% (v/v) of total EO content into hydrolate and carvacrol as a dominant component. The hydrolate showed a good antimicrobial activity against bacteria and yeasts. It exhibited a synergistic effect with itraconazole against Candida krusei, and an additive effect with tetracycline against methicillin-resistant Staphylococcus aureus strains. Hydrolate changed the membranes permeability of bacteria and yeasts and altered mitochondrial function of yeasts. Conclusions Our study extends the knowledge by exploiting non-conventional antimicrobial agents to fight the emergence of antibiotic resistance.